Robotic Delivery System for Multi-Storey Condominium Complexes - Nicholas Teo Yong Yeow; Tew Yiqi; Yeoh, Sing Hsia; Yiauw Kah Haur; Lim Ming Jun; Ng Yik Heng; Tan Hui Shan (Journal of Electronic Voltage and Application, 2022)
In certain environments like condominium complexes, couriers are only allowed to drop off their payloads at designated drop-off stations instead of delivering it directly to the recipient. This practice has become more common in condominium during the Covid-19 pandemic, in part due to government SOPs encouraging their adoption. This project aims to develop a partially automated delivery system using robot couriers that would deliver the payloads from the drop-off stations directly to the recipient, removing the need for manual collection. The system is made up of a central database, a simulated delivery robot and two Android applications for interfacing with the system. The applications and database are used to arrange the delivery request and the robot services it by navigating the complex. The Robotic Multi-Storey Delivery System is able to perform deliveries within a controlled condominium environment, use QR codes to verify recipients and displays the system status clearly on a dashboard which is linked to a database. It is a fully software project where a simulated environment for robot delivery system was developed.